IMPLEMENTASI STRATEGI PEMBELAJARAN GURU UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN IPS DI KELAS IV SEKOLAH DASAR - Yakin, Al; Apriani, Homi; Zakiah, Linda; Yunus, Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student participation is a crucial element in learning, particularly in Social Studies (IPS) in elementary schools. Lack of participation can hinder the effective achievement of learning objectives. This study aims to identify and analyze strategies implemented by fourth-grade elementary school teachers to increase student participation in social studies learning. The research method used was a case study with in-depth interviews with fourth-grade elementary school teachers at SDN Cempaka Putih Barat 17, Central Jakarta. The main findings indicate that teachers use various strategies, including linking material to students' daily lives, implementing active learning models such as Project Based Learning (PjBL), and utilizing engaging learning media. Challenges faced include differences in student abilities and time constraints. The solutions implemented are varied learning and gradual mentoring. In conclusion, adaptive and student-centered teacher strategies have proven effective in increasing student participation, although implementation needs to be tailored to students' individual needs.